Histomorphometric Quantitative Evaluation of Long-Term Risedronate Use in a Knee Osteoarthritis Rabbit Model - Fernández-Martín, Silvia; González-Cantalapiedra, Antonio; Permuy, María; García-González, Mario; López-Peña, Mónica; Muñoz, Fernando (Frontiers in Veterinary Science, 2021)
Osteoarthritis (OA) treatment is a major orthopaedic challenge given that there is no ideal drug capable to reverse or stop the progression of the OA. In that regard, bisphosphonates have been proposed as potential disease-modifying drugs due to their possible chondroprotective effect related to obtaining a greater subchondral bone quality. However, their effectiveness in OA is still controversial and additionally, there is little evidence focused on their long-term effect in preclinical studies. The aim of this study was to evaluate the risedronate quantitative effect on articular and subchondral periarticular bone by histomorphometry, in an experimental rabbit model in an advanced stage of OA. Twenty-four adult New Zealand rabbits were included in the study. OA was surgically induced in one randomly chosen knee, using the contralateral as healthy control. Animals were divided into three groups (n = 8): placebo control group, sham surgery group and risedronate-treated group. After 24 weeks of treatment, cartilage and subchondral femorotibial pathology was evaluated by micro-computed tomography (micro-CT) and undecalcified histology. The research results demonstrated that the experimental animal model induced osteoarthritic changes in the operated joints, showing an increased cartilage thickness and fibrillation associated with underlying subchondral bone thinning and decreased trabecular bone quality. These changes were especially highlighted in the medial tibial compartments as a possible response to surgical instability. Regarding the trabecular analysis, significant correlations were found between 2D histomorphometry and 3D imaging micro-CT for the trabecular bone volume, trabecular separation, and the trabecular number. However, these associations were not strongly correlated, obtaining more precise measurements in the micro-CT analysis. Concerning the long-term risedronate treatment, it did not seem to have the capacity to reduce the osteoarthritic hypertrophic cartilage response and failed to diminish the superficial cartilage damage or prevent the trabecular bone loss. This study provides novel information about the quantitative effect of long-term risedronate use on synovial joint tissues.